(untitled) (Journal of Imam Al-Kadhim College, 2024)
The main goal of this research is to explain the concept of underage marriage, and to identify the factors that lead to underage marriage and its consequences, as well as to explain underage marriage in Iraqi legislation and the medical position on it. The research problem was crystallized in answering the following question, “What is the reality of underage marriage in Iraqi law?” The research reached a set of results, the most important of which is that the age of puberty in women differs from one woman to another, and that puberty in one region differs from what it is in other regions, and that the lowest age in which they reach Women’s puberty is nine years of age, and women’s puberty may be delayed, reaching the age of fifteen or more in some cold regions. The law makers stipulate that the two contracting parties have legal capacity and that this legal capacity is only due to reason and maturity. If the marriage takes place before legal legal capacity is achieved, it is subject to the system of guardianship and guardianship over the contracting parties because they have not yet reached an appropriate age that qualifies them to know what is beneficial to them because their full legal legal capacity has not been achieved. Rather, it is considered legal for someone who has not reached legal legal capacity. Incomplete and therefore subject to the guardianship or guardianship system in law.